Mindfulness in the Brazilian National Health System (SUS): Why Training Instructors Is Not Expensive but Strategic and Cost-Effective - Marcelo Demarzo (Qeios, 2026)
BACKGROUND: It is often argued that training mindfulness instructors would be too expensive to be feasible within a public health system such as Brazil’s Unified Health System (SUS). This essay challenges that perception by combining epidemiological estimates, illustrative cost analysis, and evidence from national and international experiences. METHODS: Using population-based planning benchmarks, we estimated the number of instructors required for nationwide implementation of mindfulness-based interventions (MBIs) in the SUS. We calculated training costs and added illustrative estimates of ongoing maintenance (refresher training, attrition replacement) and delivery costs under two explicit scenarios (task-shifting within existing teams vs. additive dedicated time), comparing all estimates to key health expenditures. Evidence from recent systematic reviews and Brazilian trials of the Mindfulness-Based Health Promotion (MBHP) program was also reviewed, alongside contrary international evidence. RESULTS: Between 8,400 and 11,200 instructors would be required to cover the SUS population, at an estimated one-time training cost of R$126-168 million (Brazilian reais;